The effectiveness of constructed wetland method in greywater treatment using Purun danau (Lepironia articulata) plant - Dwi Puspa Oktaningtyas; Adian Khoironi; Adhelia Intan Sabhira (Journal of Bioresources and Environmental Sciences, 2024)
The use of clean water around the world continues to increase along with the increase in population and is increasing when the whole world is hit by the COVID-19 pandemic. Therefore, research is carried out to treat greywater waste effectively in a simple and inexpensive way. The method used in this study is a single method, namely filtration (a mixture of soil and sand, activated char- coal and gravel), Lepironia articulata and a combination of the two methods, namely constructed wetland subsurface vertical flow. The results of this study showed a decrease in BOD and COD levels reaching 97%, 88% phosphate, 18% pH and 95% MBAS in the constructed wetland. This is due to the synergistic interaction between plants, media and microorganisms in removing pollutants effectively. This research needs to be developed further and explore the capabilities of each constructed wetland element, especially the Lepironia articulata.